ANALISIS PERBANDINGAN KUALITAS PRODUK, KUALITAS PELAYANAN, CITA RASA DAN KEPUASAN KONSUMEN MIE GACOAN DAN MIE KOBER DI SIDOARJO - Sari, Eka Novita; Maduwinarti, Ayun; Pudjianto, Agung (Research Journal of Social Science and Economics, 2025)
The marketing objectives of these two culinary businesses equally target all age groups, but especially students who are often curious about new items that are presented in an unusual and creative way, resulting in a boom in society along with the main menu. will be a very interesting level of spicy food. Mi Gacoan and Mie Kober serving similar types of cuisine have become rivals, competing with each other to attract customers' attention and capture most of the market by providing high-quality goods, high-quality service, delicious food and high-quality prices. This study uses a quantitative research method approach. The quantitative research method is a type of research that is systematic, planned and clearly structured from the start to the creation of the research design. Quantitative research methods in this study using comparative research. In this research, the writer will try to compare some of the variables that are the focus of the observations, namely the variables of Product Quality, Service Quality, Taste and Consumer Satisfaction. The population in this study were all consumers of Mie Gacoan and Mie Kober in Sidoarjo, based on the results of a comparative analysis using the independent T test showing that there were no significant differences in product quality, service quality, taste and consumer satisfaction, but based on the average value the average of the two places showed no significant difference. It is hoped that business owners of Mie Gacoan and Mie Kober can maintain the Convenience Service more, because most consumers in these two places are satisfied with the ease of repair if there is a product that does not match the order. Business owners also need to improve quality so that consumers can continue to make repeated purchases at both Mie Gacoan and Mie Kober